(untitled) (Bangladesh Journal of Neuroscience, 2026)
Hirayama disease is a rare self-limiting benign disorder. It is a focal, lower motor neuron type of disease commonly affecting young males in their second and third decades of age. It is most commonly seen in Asian countries like India, Japan and China but in Bangladesh, there was no available data for incidence of the disease. MRI of the cervical spine in flexion will reveal the cardinal features of Hirayama disease. Here we report three cases of Hirayama disease presented at the outpatient department of Bangabandhu Sheikh Mujib Medical University, Dhaka. Among Three Cases two of them presented with asymmetrical distal bilateral upper limb weakness and wasting and one with unilateral involvement. Though Hirayama disease is benign and usually a self-limiting disorder but requires early diagnosis to reduce the progression of the disease. The use of Cervical Collar and physiotherapy can reduce the progression.